Enhancing interoperability to facilitate implementation of REDD+: case study of Mexico. Issue 1 (2nd January 2017) - Vargas, Rodrigo; Alcaraz-Segura, Domingo; Birdsey, Richard; Brunsell, Nathaniel A.; Cruz-Gaistardo, Carlos O.; de Jong, Bernardus; Etchevers, Jorge; Guevara, Mario; Hayes, Daniel J.; Johnson, Kristofer; Loescher, Henry W.; Paz, Fernando; et al.
ABSTRACT: There is an increasing need for approaches to determine reference emission levels and implement policies to address the objectives of Reducing Emissions from Deforestation and Forest Degradation, plus improving forest management, carbon stock enhancement and conservation (REDD+). Important aspects of approaching emissions reductions include coordination and sharing of technology, data, protocols and experiences within and among countries to maximize resources and apply knowledge to build robust monitoring, reporting and verification (MRV) systems. We propose that enhancing the multiple facets of interoperability could facilitate implementation of REDD+ programs and actions. For this case, interoperability is a collective effort with the ultimate goal of sharing and using information to produce knowledge and apply knowledge gained, by removing conceptual, technological, organizational and cultural barriers. These efforts must come from various actors and institutions, including government ministries/agencies, scientific community, landowners, civil society groups and businesses. Here, we review the case of Mexico as an example of evolving interoperability in developing countries, and highlight challenges and opportunities for implementation of REDD+. Country-specific actions toward a higher degree of interoperability can be complex, expensive and even risky. These efforts provide leadership opportunities and will facilitate science–policy integration for implementation of REDD+, particularly in developing counties.